Challenges of Embedded Systems Teaching in Electronic Engineering Studies - Nakutis, Ž.; Saunoris, M. (Elektronika ir Elektrotechnika, 2010)
An overview of the key challenges that are faced during teaching of embedded systems (ES) in electronic engineering context is given in the paper. The study of the last three years final bachelor projects defended in electronic engineering (EE) branch at Kaunas university of technology, Telecommunications and Electronics Faculty is conducted. The goal of the study was to summarize what ES related tools and solutions students do utilize in their projects and how professional they are in their reports. The intention of this analysis is not only to reveal the extent of ES penetration of EE field but also to estimate the correlation between tools and technologies taught and really selected by students in their final qualification proof project. The results can among other issues be used to estimate the success of the group of courses targeting ES design.